2008
DOI: 10.1021/jp807609d
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of the Carbon-13 and Deuterium Kinetic Isotope Effects in the Cl and OH Reactions of CH3F

Abstract: A laser flash photolysis-resonance fluorescence technique has been employed to determine absolute rate coefficients for the CH3F + Cl reaction in N2 bath gas in the temperature range of 200-700 K and pressure range of 33-133 hPa. The data were fitted to a modified Arrhenius expression k(T) = 1.14 x 10(-12) x (T/298)2.26 exp{-313/T}. The OH and Cl reaction rates of (13)CH3F and CD3F have been measured by long-path FTIR spectroscopy relative to CH3F at 298 +/- 2 K and 1013 +/- 10 hPa in purified air. The FTIR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 89 publications
2
8
2
Order By: Relevance
“…The calculated value of the rate constant for the hydrogen abstraction reaction CH 3 F + Cl of 3.3×10 −13 cm 3 molecule −1 s −1 at 298 K is very close to that of 3.5×10 −13 cm 3 molecule −1 s −1 unamimously recommended by the IUPAC and NASA [12–14] evaluations of the kinetic data. Our calculated value of k (CH 3 F+Cl) at room temperature is very close to the reported results of 2.7×10 −13 derived by Hitsuda et al [19], 3.2×10 −13 of Wallington et al [18], 3.4×10 −13 of Tuazon et al [17], 3.5×10 −13 of Sarzyński et al [22], (3.5–3.9) ×10 −13 of Marinkovic et al [21], 3.6×10 −13 of Manning and Kurylo [15], and that of 3.8×10 −13 cm 3 molecule −1 s −1 of Tschuikow-Roux et al [16] after correction taking into account the current value of the rate constant for the reference reaction CH 4 + Cl [65]. Figure 3 shows a comparison of calculated values of k (CH 3 F+Cl) with the available results of experimental measurements in a wide temperature range.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The calculated value of the rate constant for the hydrogen abstraction reaction CH 3 F + Cl of 3.3×10 −13 cm 3 molecule −1 s −1 at 298 K is very close to that of 3.5×10 −13 cm 3 molecule −1 s −1 unamimously recommended by the IUPAC and NASA [12–14] evaluations of the kinetic data. Our calculated value of k (CH 3 F+Cl) at room temperature is very close to the reported results of 2.7×10 −13 derived by Hitsuda et al [19], 3.2×10 −13 of Wallington et al [18], 3.4×10 −13 of Tuazon et al [17], 3.5×10 −13 of Sarzyński et al [22], (3.5–3.9) ×10 −13 of Marinkovic et al [21], 3.6×10 −13 of Manning and Kurylo [15], and that of 3.8×10 −13 cm 3 molecule −1 s −1 of Tschuikow-Roux et al [16] after correction taking into account the current value of the rate constant for the reference reaction CH 4 + Cl [65]. Figure 3 shows a comparison of calculated values of k (CH 3 F+Cl) with the available results of experimental measurements in a wide temperature range.…”
Section: Resultssupporting
confidence: 91%
“…The calculated values of the rate constants k (CD 3 X+Cl) are distinctly lower compared with the values of their counterparts, k (CH 3 X+Cl), especially at low temperatures. On the other hand, the values derived in this study and the reported values of KIE [21] calculated at the different levels of theory are higher than those estimated experimentally. It may suggest that the stabilization by collisions of the molecular complexes formed during the reaction should be explicitly considered in the description of the reaction kinetics.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…This phenomenon results from conformational sampling due to excess (or even zero point) vibrational energy residing in the reactant that allows the traversal of the dividing surface between reactants and products at a point distant from the first‐order saddle point 19. 20 In spite of the potential complications arising from the use of transition structures or first‐order saddle points to describe the transition state, it appears to be a robust approximation in most cases.…”
Section: How Kies Inform Mechanismmentioning
confidence: 99%